2022
DOI: 10.1002/jcla.24648
|View full text |Cite
|
Sign up to set email alerts
|

LAMTOR3 is a prognostic biomarker in kidney renal clear cell carcinoma

Abstract: Objective The objective of the study was to investigate the expression of LAMTOR3 in kidney renal clear cell carcinoma (KIRC) and its clinical significance. Methods The expression of LAMTOR3 in KIRC and its relationship with clinical features were analyzed using the UALCAN online database. The results were verified using KIRC gene chip data and clinical specimens. The prognosis of KIRC patients was analyzed with the GEPIA2 database. GO, KEGG, and GSEA analyses were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In addition, LAMTOR3 expression was significantly decreased in renal clear cell carcinoma compared with normal renal tissue. LAMTOR3 may be a potential marker for the diagnosis and treatment of renal clear cell carcinoma (Gong et al 2022 ). Song et al ( 2015 ) found that LAMTOR3 polymorphisms may be a potential biomarker of genetic susceptibility to gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LAMTOR3 expression was significantly decreased in renal clear cell carcinoma compared with normal renal tissue. LAMTOR3 may be a potential marker for the diagnosis and treatment of renal clear cell carcinoma (Gong et al 2022 ). Song et al ( 2015 ) found that LAMTOR3 polymorphisms may be a potential biomarker of genetic susceptibility to gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tubulin alpha-I a cell division, cell movement, microtubule based process, cell junction organization, cytoskeleton organization and cytoskeleton dependent intracellular transport upregulated in BC tissues [66], GC [67] PT involved in infiltration of macrophages to the tumor microenvironment [67], involved in EMT related to re-organization of cell-cell contact [68] overexpression was correlated with poor overall survival and a more aggressive phenotype in GC [67] [72] and regulation of mitochondrial membrane remodeling [73] highly upregulated in BC, CRC tissue and cell lines [72] PT positive correlation with p-Akt and CDK2 [72], c-Jun [73] important in tumorigenesis, poor prognosis in ER+, ER+PR+, HER2+, and TNBC, inhibits apoptosis by activation of c-Jun and Bcl-3 [73] [74] overexpressed in various cancers: PCa [74], pancreatic ductal carcinoma [75], ovarian carcinoma [76]; downregulated in human cervical carcinoma cells [77] PT OXPHOS; lipid metabolism signaling [74]; downregulation could induce EMT [77] aggressive tumor progression, poor prognosis, increases cell proliferation, growth, colony formation, migration, invasion, and cell cycle [74]; silencing induces reduction of cell proliferation, invasion, migration, and enhances apoptosis [76], cells being unable to grow or proliferate in response to extracellular growth factors [78] LAMTOR3/ MAPKSP1/MP1 Late endosomal/lysosomal adaptor, MAPK and MTOR activator 3/mitogen activated protein kinase scaffold protein 1/MEK partner 1 member of the Ragulator complex involved in multiple signaling pathways that acts as a scaffold protein complex [79] overexpressed in ER+ and ER-BC cell lines and in non-tumorigenic mammary epithelial cell lines [80]; downregulated in KIRC [79] PT considered to be a convergence point for MAPK and mTOR pathways [81]; targeting MEK1/MP1/ERK1/BCL2 axis may improve clinical outcome of MLCC patients [82] required for pro-survival signaling from PI3K/AKT pathway in ER+ BC cells [80]; upregulation induces BCL2 expression (anti-apoptotic protein)…”
Section: Ptbp1/hnrnp1mentioning
confidence: 99%